Trends and Impacts of Different Barriers on Bangladeshi RMG Industryâs Sustainable Development - Hasan, Md Morshadul; Parven, Tanjina; Khan, Shajib; Mahmud, Appel; Yajuan, Lu (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2018)
The main objective of this research is to investigate the trends and impacts of different barriers to Bangladeshi Ready-Made Garments (RMG) industryâs growth and development. The influencing factors or barriers have identified and their impact has explored in this research. The trends of identified factors have shown with their specific reasons. Data of this research have collected from the apparel industry in Dhaka and Gazipur City Corporation area using different techniques based on random sampling from its fixed population specified by BGMEA. It has been found that most of the factors have a decreasing trend with mostly moderate impacts on the RMG industryâs growth and development. The most important reason for this research is to help the investors who are going to invest in Bangladeshi apparel sector by showing the actual scenario. There has a few past research related to the impact on growth and development.Â https://doi.org/10.21632/irjbs.11.3.245-260